The Influence of Various Substrates on Power Generation in The Operation of Yeast Microbial Fuel Cells - Christwardana, Marcelinus; Joelianingsih, J.; Yoshi, Linda Aliffia (Reaktor, 2022)
Several carbon substrates were tried, including glucose commercial, pro analysis glucose, commercial sugar, and yeast extract - peptone - d glucose (YPD) medium to improve the efficiency of the single chamber microbial fuel cell (MFC). The power production of various electron donors was investigated using baker yeast Saccharomyces cerevisiae. Voltage and power density generation were used to establish the pattern of substrate use. In addition, electrochemical analysis of the anodic biofilm was performed. S. cervisiae was shown to successfully consume YPD medium by anode respiration with a higher power density of 18.40±1.98 mW/m2, followed by pro analysis glucose (9.41±1.15 mW/m2), commercial glucose (1.30±0.10 mW/m2), and commercial sugar (0.04±0.01 mW/m2). Furthermore, a clear relationship was established between power density generating rate and voltage output. Voltages produced were 0.16±0.02 V, 0.13±0.03 V, 0.03±0.01 V, 0.01±0.00 V for YPD medium, pro analysis glucose, commercial glucose, and commercial sugar, respectively in MFC. The weight of biofilm indicated that yeast attachment was significantly more common in YPD medium than in other MFC-operated media. This study discovered that the substrate type in the anodic compartment regulates the formation of anodic biofilm.